2011
DOI: 10.5600/mmrr.002.01.a01
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Utilization in the Texas Medicaid Emergency Waiver

Abstract: Objective: To estimate the enrollment and emergency department (ED) utilization in TexKat, the TexasMedicaid emergency waiver implemented following Hurricane Katrina. Data Sources:Individual-level enrollment and utilization data from the 2005 Medicaid Analytic Extract. Study Design: Descriptive analysis is performed on variables that describe enrollment levels, the demographic characteristics of enrollees, and the most common diagnoses in ED visits. A Poisson regression model is also employed to quantify the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Nearly all of the research on ED and inpatient utilization following disasters has focused on the period immediately following the event. Hurricane Katrina was associated with immediate increased ED visit rates in both the New Orleans area (Sharma et al 2008) and in Texas (Mortensen et al 2008;Quast et al 2012), while seniors in a Medicare Advantage plan who lived in New Orleans before Katrina were found to have 21% higher ED visits rates during the year after than the year prior to the storm (Burton et al 2009). End stage renal disease patients in affected areas had higher hospitalization rates immediately following Katrina (Anderson et al 2009;Howard et al 2012) while the study of Medicare Advantage plan members found one-year hospitalization rates 23% higher than in the year prior to Katrina (Burton et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all of the research on ED and inpatient utilization following disasters has focused on the period immediately following the event. Hurricane Katrina was associated with immediate increased ED visit rates in both the New Orleans area (Sharma et al 2008) and in Texas (Mortensen et al 2008;Quast et al 2012), while seniors in a Medicare Advantage plan who lived in New Orleans before Katrina were found to have 21% higher ED visits rates during the year after than the year prior to the storm (Burton et al 2009). End stage renal disease patients in affected areas had higher hospitalization rates immediately following Katrina (Anderson et al 2009;Howard et al 2012) while the study of Medicare Advantage plan members found one-year hospitalization rates 23% higher than in the year prior to Katrina (Burton et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Financing also favours male-dominated sectors, including energy and transport, whereas female-dominated sectors such as agriculture or textile manufacturing are rarely acknowledged 33. For this reason, social protection support for alternative income sources, including skill development, training and household asset management, should be promoted for women,34 as well as expanding access to formal credit with reduced interest rates 35…”
Section: Introductionmentioning
confidence: 99%
“… 33 For this reason, social protection support for alternative income sources, including skill development, training and household asset management, should be promoted for women, 34 as well as expanding access to formal credit with reduced interest rates. 35 …”
Section: Introductionmentioning
confidence: 99%